Why students become more engaged or more disengaged during the semester: A self-determination theory dual-process model. (June 2016) - Jang, Hyungshim; Kim, Eun Joo; Reeve, Johnmarshall
Abstract: We adopted a dual-process model within a self-determination theory framework to investigate why students sometimes veer toward a longitudinal trajectory of rising classroom engagement during the semester and why they other times tend toward a trajectory of rising disengagement. Measures of perceived autonomy support, perceived teacher control, need satisfaction, need frustration, engagement, and disengagement were collected from 366 (174 females, 192 males) Korean high-school students using a three-wave longitudinal research design. Multi-level structural equation modeling analyses found that perceived autonomy support predicted longitudinal changes need satisfaction which predicted changes in engagement and also that perceived teacher control predicted longitudinal changes need frustration which predicted changes disengagement. Reciprocal effects also emerged in that extent of disengagement predicted both longitudinal increases in students' perceptions of teacher control and decreases in perceptions of teacher autonomy support. We conclude that students tend toward a semester-long trajectory of rising engagement when they perceive their teachers to be autonomy supportive and need satisfying while they tend toward a trajectory of rising disengagement when they perceive their teachers to be controlling and need frustrating. Highlights: We investigated why students veer toward a trajectory of rising engagement. Autonomy support and need satisfaction predicted rising classroom engagement. We also investigated why students veer toward a trajectory of rising disengagement. Teacher control and need frustration predicted rising classroom disengagement. Reciprocal effects emerged; disengagement predicted changes in perceived motivating style.